Effect of paint removal with kilowatt level nanosecond pulsed laser on microstructure and mechanical properties of stainless steel - Yoo, Hyun Jong; Park, Hyoungwon; Kim, Jeoung Han; Park, Changkyoo (Optics and Laser Technology, 2023)
In this study, a kilowatt level nanosecond pulsed laser is used to remove the paint layer on the 304L stainless steel (SS304L) surface. Different number of repetitions of laser paint removal (LPR) processes were applied, and their corresponding influences to SS304L were analyzed with various analytic methods. An electron probe X-ray microanalyzer (EPMA) confirmed complete removal of the paint layer for the number of LPR process repetitions of nine (LPR 9) and twelve (LPR 12) times. Also, an LPR-induced microstructural modification was investigated using electron backscatter diffraction (EBSD), revealing the smaller grain size and larger strain rate for the larger number of LPR process. Moreover, the surface properties including the surface profile and residual stress, and mechanical properties were characterized before and after the LPR processes. For the LPR 9 and LPR 12, a decrease in the elongation and an increase in the surface microhardness were observed, originated from the grain refinement and high strain rate.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 304L stainless steel; Laser cleaning; Mechanical properties; Microstructure; Paint removal